2019
DOI: 10.4103/sajc.sajc_276_18
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profile in Indian primary myelofibrosis patients and its clinical implications

Abstract: Background: Primary myelofibrosis (PMF) is a myeloproliferative neoplasm (MPN) characterized by abnormal proliferation of megakaryocytes, bone marrow fibrosis, and extramedullary hematopoiesis. We did mutation profile of 50 patients of PMF and tried to correlate it with initial clinical presentation of these patients. Materials and Methods: All new and follow up patients who were diagnosed as PMF based on WHO 2016 definition of PMF were included. Mutation profile of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[18][19][20] Moreover, a study in an Indian cohort of 50 PMF patients showed that 64% of the patients harbored the JAK2 V617F mutation, 26% of the patients harbored mutations in the CALR gene, and 2% in the MPL gene. 10 Of the 274 samples tested, we observed the JAK2 V617F exon 14 mutation in only 48 patients (17.5%). One plausible explanation for the low percentage of samples harboring the JAK2 V617F mutation in our cohort could be that for most of the samples referred to our lab, the hematologists performed the JAK2 V617F mutation testing elsewhere; only JAK2 V617F negative samples were referred to our lab to test for other driver mutations by the targeted NGS assay.…”
Section: Prevalence Of Jak2 Calr and Mpl Mutationsmentioning
confidence: 75%
See 1 more Smart Citation
“…[18][19][20] Moreover, a study in an Indian cohort of 50 PMF patients showed that 64% of the patients harbored the JAK2 V617F mutation, 26% of the patients harbored mutations in the CALR gene, and 2% in the MPL gene. 10 Of the 274 samples tested, we observed the JAK2 V617F exon 14 mutation in only 48 patients (17.5%). One plausible explanation for the low percentage of samples harboring the JAK2 V617F mutation in our cohort could be that for most of the samples referred to our lab, the hematologists performed the JAK2 V617F mutation testing elsewhere; only JAK2 V617F negative samples were referred to our lab to test for other driver mutations by the targeted NGS assay.…”
Section: Prevalence Of Jak2 Calr and Mpl Mutationsmentioning
confidence: 75%
“…Therefore, the detection of these somatic mutations aids the clinician in patient management. JAK2 mutations are observed in the majority of cases in the Indian subcontinent; 10 mutations in the MPL and CALR genes account for 30-40% of Phnegative chronic MPNs. 6 Targeted capillary (or Sanger) sequencing can be used to check these mutations; however, this method is limited by its relatively low sensitivity (20%) for the detection of MPNs as certain low-depth mutations may be missed.…”
Section: Introductionmentioning
confidence: 99%